Proliferation State and Polo‐Like Kinase1 Dependence of Tumorigenic Colon Cancer Cells123. (20th August 2012) - Francescangeli, Federica; Patrizii, Michele; Signore, Michele; Federici, Giulia; Di Franco, Simone; Pagliuca, Alfredo; Baiocchi, Marta; Biffoni, Mauro; Ricci Vitiani, Lucia; Todaro, Matilde; De Maria, Ruggero; Zeuner, Ann
Abstract: Tumor‐initiating cells are responsible for tumor maintenance and relapse in solid and hematologic cancers. Although tumor‐initiating cells were initially believed to be mainly quiescent, rapidly proliferating tumorigenic cells were found in breast cancer. In colon cancer, the proliferative activity of the tumorigenic population has not been defined, although it represents an essential parameter for the development of more effective therapeutic strategies. Here, we show that tumorigenic colon cancer cells can be found in a rapidly proliferating state in vitro and in vivo, both in human tumors and mouse xenografts. Inhibitors of polo‐like kinase1 (Plk1), a mitotic kinase essential for cell proliferation, demonstrated maximal efficiency over other targeted compounds and chemotherapeutic agents in inducing death of colon cancer‐initiating cells in vitro. In vivo, Plk1 inhibitors killed CD133 + colon cancer cells leading to complete growth arrest of colon cancer stem cell‐derived xenografts, whereas chemotherapeutic agents only slowed tumor progression. While chemotherapy treatment increased CD133 + cell proliferation, treatment with Plk1 inhibitors eliminated all proliferating tumor‐initiating cells. Quiescent CD133 + cells that survived the treatment with Plk1 inhibitors could be killed by subsequent Plk1 inhibition when they exited from quiescence. Altogether, these results provide a new insight into the proliferative status of colon tumor‐initiating cells both in basal conditions and in response to therapy and indicate Plk1 inhibitors as potentially useful in the treatment of colorectal cancer. Stem Cells 2012;30:1819–1830